Oxazol-5-(4H)-Ones. Part 1. Synthesis and Reactivity as 1,3-dipoles - Piperno, Anna; Scala, Angela; Risitano, Francesco; Grassi, Giovanni (Current Organic Chemistry, 2014)
The interest in the chemistry of saturated oxazolones continues unabated in virtue of their usefulness as intermediates in the synthesis of highly substituted heterocycles. This review attempts to present the prolific development of recent years in this area and gives a critical and unified account of azlactones under the following headings: saturated oxazolone synthesis; generation of cyclic azomethine ylide intermediates and relative oxazolone/imine cycloadditions and oxazolone/alkene cycloadditions; general overview of their usefulness in the functionalization of carbon nanomaterials and in the synthesis of pharmaceutically and biologically intriguing compounds. A particular attention is reserved to the enantioselective oxazolone cycloaddition processes for both known synthetic approaches: chiral induction by metal catalysts and asymmetric activation by organocatalysts.
Keywords: proteasome inhibitors